Accumulation of Four Electrons on a Terphenyl (Bis)disulfide. Issue 72 (9th November 2022) - Schmid, Lucius; Fokin, Igor; Brändlin, Mathis; Wagner, Dorothee; Siewert, Inke; Wenger, Oliver S.
Abstract: The activation of N2, CO2 or H2 O to energy‐rich products relies on multi‐electron transfer reactions, and consequently it seems desirable to understand the basics of light‐driven accumulation of multiple redox equivalents. Most of the previously reported molecular acceptors merely allow the storage of up to two electrons. We report on a terphenyl compound including two disulfide bridges, which undergoes four‐electron reduction in two separate electrochemical steps, aided by a combination of potential compression and inversion. Under visible‐light irradiation using the organic super‐electron donor tetrakis(dimethylamino)ethylene, a cascade of light‐induced reaction steps is observed, leading to the cleavage of both disulfide bonds. Whereas one of them undergoes extrusion of sulfur to result in a thiophene, the other disulfide is converted to a dithiolate. These insights seem relevant to enhance the current fundamental understanding of photochemical energy storage. Abstract : Charge accumulation is relevant for applications in solar energy conversion. Here, we present an electron acceptor that is able to store up to four electrons by taking advantage of the uncommon phenomenon of potential inversion.